2012
DOI: 10.1186/1475-2875-11-90
|View full text |Cite
|
Sign up to set email alerts
|

The association between malnutrition and the incidence of malaria among young HIV-infected and -uninfected Ugandan children: a prospective study

Abstract: BackgroundIn sub-Saharan Africa, malnutrition and malaria remain major causes of morbidity and mortality in young children. There are conflicting data as to whether malnutrition is associated with an increased or decreased risk of malaria. In addition, data are limited on the potential interaction between HIV infection and the association between malnutrition and the risk of malaria.MethodsA cohort of 100 HIV-unexposed, 203 HIV-exposed (HIV negative children born to HIV-infected mothers) and 48 HIV-infected ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 38 publications
3
64
1
Order By: Relevance
“…8 and a specificity of 93% (95%CI 84-97%) to predict malaria in this cohort. However, a higher grade fever (T > 38.0 °C) was present in only 5% of students with malaria, which was not statistically significantly different from negative controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 and a specificity of 93% (95%CI 84-97%) to predict malaria in this cohort. However, a higher grade fever (T > 38.0 °C) was present in only 5% of students with malaria, which was not statistically significantly different from negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…22 We did not observe an association between underweight and malaria in our cross-sectional survey, similar to a recent study in Ethiopia 11 but unlike other studies from Uganda. 7,8 A among children under 5. Our study, which focused on school-aged children rather than children under 5, likewise found high rates of underweight, consistent with widespread food insecurity across childhood age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wealth indices often include food security and house construction variables, 34 but these factors may be independently associated with malaria in the study area. 35,36 To evaluate whether including food security and house construction variables altered the association between the wealth index and malaria outcomes, Wealth Index II additionally included five variables: 10) main roof material, 11) main wall material, 12) main floor material, 13) frequency of meat consumption, and 14) number of meals per day. Households were ranked by wealth scores and grouped into tertiles.…”
Section: Methodsmentioning
confidence: 99%
“…It can be one of the main etiological factors of diarrhoea and this latter can lead to poor absorption in the gut, lack of appetite vomiting etc which can lead to malnutrition in general and micronutrient insufficiencies in particular; for instance iron deficiency leading to anemia in children (6). Furthermore, Malnutrition is a predisposing factor to vulnerability to common infections which in this context is malaria (4,14). The cross sectional aspect of this study and the fact that it was a documentary investigation did not permit the advent of these relationships though a 69 moderate correlation was noted between malnutrition and diarrhoea.…”
Section: Discussion:-mentioning
confidence: 99%